Early Cretaceous Ostracoda (Crustacea) from the Lisangou Formation in the Guyang Basin, North China: Implications for biostratigraphy and palaeoenvironment - Ya-Qiong Wang; Hua-Zheng Zhu; Robin J. Smith; Byung-Do Choi (Palaeoworld, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Novel symbioses between reef fishes and serpulid polychaetes in the Caribbean Sea - Morgan F. Bennett-Smith; Elizabeth McNamee; Samantha Masih; Timothy Lis; Mason Murchison; Allison Cinelli; Toshith Bhaumik; Catheline Y. M. Froehlich; Anna DeLoach; Ned DeLoach; Ninon Martinez; Peter M. Buston; et al. (Symbiosis, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Corrigendum to ‘Corenet: A flexible framework for generating and prioritising core cycle network designs’ [Journal of Transport Geography 122 (2026) 104148] - Zhao Wang; Hang Hu; Hussein Mahfouz; Juan Pablo Fonseca-Zamora; Martin Lucas-Smith; Dustin Carlino; Angus Calder; Congying Hu; Matthew Davis; Joseph Talbot; Robin Lovelace (Journal of Transport Geography, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Corenet: A flexible framework for generating and prioritising core cycle network designs - Zhao Wang; Hang Hu; Hussein Mahfouz; Juan Pablo Fonseca-Zamora; Martin Lucas-Smith; Dustin Carlino; Angus Calder; Congying Hu; Matthew Davis; Joseph Talbot; Robin Lovelace (Journal of Transport Geography, 2026)

Flame retardant biomarker changes with furniture replacement after flammability standard update - Kathleen R. Attfield; Kimberly Berger; Robin E. Dodson; Deborah H. Bennett; Kathryn M. Rodgers; Rebecca Moran; Tasha Stoiber; Yunzhu Wang; Songmei Gao; Sabrina Crispo Smith; June-Soo Park; Arlene Blum; et al. (Environmental Pollution, 2026)

Citizen scientists as butterfly predators: using foraging theory to understand individual recorder behaviour - Mingrui Li; Robin J. Boyd; Chloë Smith; Richard Fox; David Roy; Jonathan Bennie; Richard H. ffrench-Constant (Ecological Modelling, 2025)

From opposition to conditional acceptance: Corporate environmental and socio-economic engagement in critical minerals mining in Michigan - Raphael Deberdt; Nicole M. Smith; Aaron Malone; Robin Bullock (Resources Policy, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Cancer Care in Post-Roe America: How Do We Move Forward? - Emily Ramonna Smith; Georgia Robins Sadler (Journal of Cancer Education, 2025)
In 2022, the Supreme Court overturned Roe v. Wade in the case of Dobbs v. Jackson Women's Health Organization. This ruling ended all federal protections for abortion, consequently reshaping the American healthcare landscape. Two years later, the impacts of this ruling on cancer care remain largely undiscussed. This reflection summarizes a literature review exploring the effects of the Dobbs decision on cancer treatment access in America. Articles were identified using databases such as PubMed, CINAHL, Westlaw Campus Research, Nexis Uni, Google Scholar, and JSTOR. Search terms included cancer, drugs, Methotrexate, access, treatment delays, Roe v. Wade, Dobbs, post-Roe, abortion, abortion-inducing, maternal health, reproductive rights, and limitations. Thirty eligible articles, published in English from 2001 to 2024, were reviewed in full text. The findings of this reflection article highlight the urgent need for the oncology community to understand the potential impact of these changes and work collectively to ensure the equal access to women's cancer care.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Limited persistence of the heat-tolerant zooxanthella, Durusdinium trenchii, in corals transplanted to a barrier reef where it is rare among natal colonies - Kira E. Turnham; Allison M. Lewis; Dustin W. Kemp; Mark E. Warner; Drew F. Wham; Robin T. Smith; Kenneth Hoadley; Patrick L. Colin; Yimnang Golbuu; Todd C. LaJeunesse (Coral Reefs, 2025)

Application of Ostracoda from the Lower Cretaceous Liupanshan group at Pingliang (NW China) – Biostratigraphy and palaeoecology - Yaqiong Wang; Byung-Do Choi; Robin J. Smith; Deyan Wu (Cretaceous Research, 2025)

Development and morphology of podocopan ostracod limbs (Crustacea) – A review - Robin James Smith (Arthropod Structure & Development, 2025)

Multiple Lineages of Transmissible Neoplasia in the Basket Cockle ( C. nuttallii ) With Repeated Horizontal Transfer of Mitochondrial DNA - Marisa A. Yonemitsu; Jordana K. Sevigny; Lauren E. Vandepas; James L. Dimond; Rachael M. Giersch; Helen J. Gurney‐Smith; Cathryn L. Abbott; Janine Supernault; Ruth Withler; Peter D. Smith; Sydney A. Weinandt; Fiona E. S. Garrett; et al. (Molecular Ecology, 2025)
Transmissible cancers are clonal lineages of neoplastic cells able to infect multiple hosts, spreading through populations in the environment as an infectious disease. Transmissible cancers have been identified in Tasmanian devils, dogs, and bivalves. Several lineages of bivalve transmissible neoplasias (BTN) have been identified in multiple bivalve species. In 2019 in Puget Sound, Washington, USA, disseminated neoplasia was observed in basket cockles ( Clinocardium nuttallii ), a species that is important to the culture and diet of the Suquamish Tribe as well as other tribes with traditional access to the species. To test whether disseminated neoplasia in cockles is a previously unknown lineage of BTN, a nuclear locus was amplified from cockles from Agate Pass, Washington, and sequences revealed evidence of transmissible cancer in several individuals. We used a combination of cytology and quantitative PCR to screen collections of cockles from 11 locations in Puget Sound and along the Washington coastline to identify the extent of contagious cancer spread in this species. Two BTN lineages were identified in these cockles, with one of those lineages (CnuBTN1) being the most prevalent and geographically widespread. Within the CnuBTN1 lineage, multiple nuclear loci support the conclusion that all cancer samples form a single clonal lineage. However, the mitochondrial alleles in each cockle with CnuBTN1 are different from each other, suggesting mitochondrial genomes of this cancer have been replaced multiple times during its evolution, through horizontal transmission. The identification and analysis of these BTNs are critical for broodstock selection, management practices, and repopulation of declining cockle populations, which will enable continued cultural connection and dietary use of the cockles by Coast Salish Tribes.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Using neuroimaging to identify sex differences in adults with sports-related concussion: a systematic review - Harry Macleod; Clare L. Smith; Robin Laycock (Brain Imaging and Behavior, 2025)
Concussion is a common injury in sports that causes neurological damage, leading to memory loss and difficulty concentrating. Insufficient recovery time may result in significant long-term harm to individuals. Several neuroimaging techniques have been used to understand the pathophysiological changes following concussion, and how long individuals need to recover before returning to play. Despite the progress in neuroimaging concussion research, few studies have considered whether females sustain different effects on the brain and how recovery from concussion might differ from males. Thus, we conducted a systematic review of the existing literature to highlight sex differences in concussion with neuroimaging techniques. By searching four different databases, studies were selected if they used a neuroimaging technique to examine sex differences following concussion in athletes over the age of 18. After screening 2295 studies from an initial search, 15 were found to match the selection criteria. Nine papers established some difference between males and females, however many of these studies were not designed to specifically examine sex differences, and hence conclusions in this regard are somewhat limited. A further common limitation among these papers was a lack of whole brain scans, instead relying on regions of interest analyses, which reduces the ability to compare studies effectively. The current systematic review has highlighted the need for future studies to specifically consider whether, and how sex influences the impact and trajectory of brain recovery from concussion. This can then help to inform suitable amendments to current concussion return-to-play protocols for male and female athletes.

Klebsiella pneumoniae in stranded California sea lions (Zalophus californianus) of Central California between 2017-2022 - Sydney N. Zotto; Robin C. Dunkin; Juliana D. Limon; Maia S. Smith; Lisabet M. Hortensius; Margaret E. Martinez; Pádraig J. Duignan; Cara Field; Esteban Soto; Dane Whitaker; Carlos Rios; Maurice Byukusenge; et al. (Frontiers in Marine Science, 2025)
Klebsiella pneumoniae is a Gram-negative, facultative anaerobic, and non-motile bacillus frequently observed in mammals. A hypermucoviscous (HMV) phenotype of K. pneumoniae is reported in stranded California sea lions (CSL) causing pleuritis and bronchopneumonia as a persistent cause of strandings. We describe an increase in cases of HMV and non-HMV K. pneumoniae in stranded CSLs along the California coast between 2017 to 2022. 2,146 live-stranded CSLs were rescued by The Marine Mammal Center (Sausalito, California). 47 of these tested positive for K. pneumoniae , with a rise in annual incidence from 0.92% (3/331) in 2017 to 8.5% (14/165) and 7.2% (23/320) in 2021 and 2022, respectively. These strandings occurred across 965 kilometers along the North-Central California coast from Bodega Bay, Sonoma, to Avila Beach, San Luis Obispo. A similar pattern was observed in beach-cast CSL carcasses by the Long Marine Laboratory (LML) Stranding Network in Santa Cruz, California who had 8 CSLs test positive for K. pneumoniae with an annual incidence rate of 2.0% (1/50) and 10.1% (7/69) in 2021 and 2022, respectively, with no cases reported prior to 2021. We applied whole-genome sequencing (WGS) to 8 isolates obtained by LML in 2022. WGS analysis revealed high nucleotide similarity between any pair of isolates. Multilocus Sequence Typing showed that all isolates belonged to Sequence type 65 and contained the K2 polysaccharide capsule and siderophore aerobactin, which are all characteristics of hypervirulent K. pneumoniae. We discuss possible causes for this trend and a need for research on K. pneumoniae in free-ranging CSLs in California.

Corrigendum to ‘Tracking Childhood Lead Exposure in Early Industrial Romanians’ [Chemosphere Volume 364 (2024) 142947] - Maya Bharatiya; Christine Austin; Manish Arora; Robin N.M. Feeney; Nicole D. Leonard; Samantha Low-Choy; Bence Paul; Andrei D. Soficaru; Jian-xin Zhao; Tanya M. Smith (Chemosphere, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Tracking Childhood Lead Exposure in Early Industrial Romanians - Maya Bharatiya; Christine Austin; Manish Arora; Robin N.M. Feeney; Nicole D. Leonard; Samantha Low-Choy; Bence Paul; Andrei D. Soficaru; Jian-xin Zhao; Tanya M. Smith (Chemosphere, 2024)

Environmental and economic sustainability assessment of the production and consumption of different types of coffee in the UK - Piya Gosalvitr; Rosa M. Cuéllar-Franca; Robin Smith; Adisa Azapagic (Sustainable Production and Consumption, 2024)

Limited spatial co-occurrence of wildfire and prescribed burning on moorlands in Scotland - Debbie Fielding; Scott Newey; Robin J. Pakeman; Dave Miller; Zisis Gagkas; Keith Matthews; Stuart W. Smith (Biological Conservation, 2024)

The diversity, distribution, and temporal stability of coral ‘zooxanthellae’ on a pacific reef: from the scale of individual colonies to across the host community - Allison M. Lewis; Caleb C. Butler; Kira E. Turnham; Drew F. Wham; Kenneth D. Hoadley; Robin T. Smith; Dustin W. Kemp; Mark E. Warner; Todd C. LaJeunesse (Coral Reefs, 2024)

Spatiotemporal carbon footprint analysis of bottled water production by ultrafiltration and reverse osmosis - Wenqi Hu; Mengqi Han; Dungang Gu; Robin Smith; Tingting Hu; Yuhang Lou; Yiran Sun; Guanghui Li; Nan Zhang; Jiaqi Lu (Journal of Water Process Engineering, 2024)

Crop rotational diversity can mitigate climate‐induced grain yield losses - Alessio Costa; Riccardo Bommarco; Monique E. Smith; Timothy Bowles; Amélie C. M. Gaudin; Christine A. Watson; Remedios Alarcón; Antonio Berti; Andrzej Blecharczyk; Francisco J. Calderon; Steve Culman; William Deen; et al. (Global Change Biology, 2024)
Diversified crop rotations have been suggested to reduce grain yield losses from the adverse climatic conditions increasingly common under climate change. Nevertheless, the potential for climate change adaptation of different crop rotational diversity (CRD) remains undetermined. We quantified how climatic conditions affect small grain and maize yields under different CRDs in 32 long‐term (10–63 years) field experiments across Europe and North America. Species‐diverse and functionally rich rotations more than compensated yield losses from anomalous warm conditions, long and warm dry spells, as well as from anomalous wet (for small grains) or dry (for maize) conditions. Adding a single functional group or crop species to monocultures counteracted yield losses from substantial changes in climatic conditions. The benefits of a further increase in CRD are comparable with those of improved climatic conditions. For instance, the maize yield benefits of adding three crop species to monocultures under detrimental climatic conditions exceeded the average yield of monocultures by up to 553 kg/ha under non‐detrimental climatic conditions. Increased crop functional richness improved yields under high temperature, irrespective of precipitation. Conversely, yield benefits peaked at between two and four crop species in the rotation, depending on climatic conditions and crop, and declined at higher species diversity. Thus, crop species diversity could be adjusted to maximize yield benefits. Diversifying rotations with functionally distinct crops is an adaptation of cropping systems to global warming and changes in precipitation.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Journals must expand access to peer review data - Olivia M. Smith; Kayla L. Davis; Robin Waterman; Riley B. Pizza; Caitlin Mack; Emily E. Conway; Kara C. Dobson; Brianna Foster; Ani E. Hristova; Julie C. Jarvey; Nan Nourn; Courtney L. Davis (Trends in Ecology & Evolution, 2024)

Harassment and killing of porpoises (“phocoenacide”) by fish‐eating Southern Resident killer whales ( Orcinus orca ) - Deborah A. Giles; Sarah J. Teman; Samuel Ellis; John K. B. Ford; Monika W. Shields; M. Bradley Hanson; Candice K. Emmons; Paul E. Cottrell; Robin W. Baird; Richard W. Osborne; Michael Weiss; David K. Ellifrit; et al. (Marine Mammal Science, 2024)
Endangered Southern Resident killer whales ( Orcinus orca ) are fish‐eaters that preferentially prey on adult Chinook salmon ( Oncorhynchus tshawytscha ). Despite being salmon specialists, individuals from all three killer whale pods (J, K, L) have been observed harassing and killing porpoises (family Phocoenidae) without consuming them. Retrospectively, we identified and analyzed 78 episodes of Southern Resident killer whales harassing porpoises between 1962 and 2020, of which 28 resulted in the porpoise's death (“phocoenacide”). Fifty‐six episodes involved harbor porpoise ( Phocoena phocoena ), 13 involved Dall's porpoise ( Phocoenoides dalli ), and the porpoise species was unreported for nine episodes. Southern Resident killer whales often targeted young porpoises that were similar in size to adult Chinook salmon. Both sexes participated in porpoise harassment. Juveniles engaged in the behavior the most; however, their rates of engagement were not found to differ significantly from most other age classes. The behavior was passed through generations and social groupings, as it was first observed in L pod and spread to the other two pods. Killer whales are highly complex animals known to exhibit social learning and cultural transmission of learned behaviors, but the reason(s) for this behavior is unknown. Hypotheses include the social and developmental benefits of play, hunting practice, or displaced epimeletic behavior.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Ice-dammed lakes and deglaciation history of the Scandinavian Ice Sheet in central Jämtland, Sweden - Carl Regnéll; Gustaf Peterson Becher; Christian Öhrling; Sarah L. Greenwood; Richard Gyllencreutz; Robin Blomdin; Jo Brendryen; Bradley W. Goodfellow; Henrik Mikko; Gunnel Ransed; Colby Smith (Quaternary Science Reviews, 2023)

Dispersal of the pesticide diuron in the Great Barrier Reef - Jennifer Skerratt; Mark E. Baird; Mathieu Mongin; Robin Ellis; Rachael A. Smith; Melanie Shaw; Andy D.L. Steven (Science of The Total Environment, 2023)

Jiří Jaromír Klemeš – His life and legacy - Petr Stehlík; Robin Smith; Petar Sabev Varbanov (Journal of Cleaner Production, 2023)

An environmental and economic sustainability assessment of coffee production in the UK - Piya Gosalvitr; Rosa M. Cuéllar-Franca; Robin Smith; Adisa Azapagic (Chemical Engineering Journal, 2023)

Peering down the sink: A review of isoprene metabolism by bacteria - Robin A. Dawson; Andrew T. Crombie; Robert S. Jansen; Thomas J. Smith; Tim Nichol; Colin Murrell (Environmental Microbiology, 2023)
Isoprene (2‐methyl‐1,3‐butadiene) is emitted to the atmosphere each year in sufficient quantities to rival methane (>500 Tg C yr −1 ), primarily due to emission by trees and other plants. Chemical reactions of isoprene with other atmospheric compounds, such as hydroxyl radicals and inorganic nitrogen species (NO x ), have implications for global warming and local air quality, respectively. For many years, it has been estimated that soil‐dwelling bacteria consume a significant amount of isoprene (~20 Tg C yr −1 ), but the mechanisms underlying the biological sink for isoprene have been poorly understood. Studies have indicated or confirmed the ability of diverse bacterial genera to degrade isoprene, whether by the canonical iso ‐type isoprene degradation pathway or through other less well‐characterized mechanisms. Here, we review current knowledge of isoprene metabolism and highlight key areas for further research. In particular, examples of isoprene‐degraders that do not utilize the isoprene monooxygenase have been identified in recent years. This has fascinating implications both for the mechanism of isoprene uptake by bacteria, and also for the ecology of isoprene‐degraders in the environments.

Finding the sweet spot: a qualitative study exploring patients’ acceptability of chatbots in genetic service delivery - Stephanie Luca; Marc Clausen; Angela Shaw; Whiwon Lee; Suvetha Krishnapillai; Ella Adi-Wauran; Hanna Faghfoury; Gregory Costain; Rebekah Jobling; Melyssa Aronson; Eriskay Liston; Josh Silver; et al. (Human Genetics, 2023)

Machine learning for geochemical exploration: classifying metallogenic fertility in arc magmas and insights into porphyry copper deposit formation - Chetan L. Nathwani; Jamie J. Wilkinson; George Fry; Robin N. Armstrong; Daniel J. Smith; Christian Ihlenfeld (Mineralium Deposita, 2022)
A current mineral exploration focus is the development of tools to identify magmatic districts predisposed to host porphyry copper deposits. In this paper, we train and test four, common, supervised machine learning algorithms: logistic regression, support vector machines, artificial neural networks (ANN) and Random Forest to classify metallogenic ‘fertility’ in arc magmas based on whole-rock geochemistry. We outline pre-processing steps that can be used to mitigate against the undesirable characteristics of geochemical data (high multicollinearity, sparsity, missing values, class imbalance and compositional data effects) and therefore produce more meaningful results. We evaluate the classification accuracy of each supervised machine learning technique using a tenfold cross-validation technique and by testing the models on deposits unseen during the training process. This yields 81–83% accuracy for all classifiers, and receiver operating characteristic (ROC) curves have mean area under curve (AUC) scores of 87–89% indicating the probability of ranking a ‘fertile’ rock higher than an ‘unfertile’ rock. By contrast, bivariate classification schemes show much lower performance, demonstrating the value of classifying geochemical data in high dimension space. Principal component analysis suggests that porphyry-fertile magmas fractionate deep in the arc crust, and that calc-alkaline magmas associated with Cu-rich porphyries evolve deeper in the crust than more alkaline magmas linked with Au-rich porphyries. Feature analysis of the machine learning classifiers suggests that the most important parameters associated with fertile magmas are low Mn, high Al, high Sr, high K and listric REE patterns. These signatures further highlight the association of porphyry Cu deposits with hydrous arc magmas that undergo amphibole fractionation in the deep arc crust.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The natural history of OTOF-related auditory neuropathy spectrum disorders: a multicenter study - Ryan K. Thorpe; Hela Azaiez; Peina Wu; Qiuju Wang; Lei Xu; Pu Dai; Tao Yang; G. Bradley Schaefer; B. Robert Peters; Kenny H. Chan; Krista S. Schatz; Joann Bodurtha; et al. (Human Genetics, 2022)

Long-term change in a high-intertidal rockweed (Pelvetiopsis californica) and community-level consequences - Robin J. Fales; Jayson R. Smith (Marine Biology, 2022)

Reflections on the scientific life and legacy of Professor Ted Milton (10 April 1954 – 8 June 2021) - Karen Anderson; Paul Aplin; Paul Curran; Jadunandan Dash; Angela Harris; Liz Rollin; John Shears; Geoff Smith; Robin Wilson (International Journal of Remote Sensing, 2021)

Different functional traits among closely related algal symbionts dictate stress endurance for vital Indo‐Pacific reef‐building corals - Kenneth D. Hoadley; Daniel. T. Pettay; Allison Lewis; Drew Wham; Chris Grasso; Robin Smith; Dustin W. Kemp; Todd LaJeunesse; Mark E. Warner (Global Change Biology, 2021)
Reef‐building corals in the genus Porites are one of the most important constituents of Indo‐Pacific reefs. Many species within this genus tolerate abnormally warm water and exhibit high specificity for particular kinds of endosymbiotic dinoflagellates that cope with thermal stress better than those living in other corals. Still, during extreme ocean heating, some Porites exhibit differences in their stress tolerance. While corals have different physiological qualities, it remains unknown whether the stability and performance of these mutualisms is influenced by the physiology and genetic relatedness of their symbionts. We investigated two ubiquitous Pacific reef corals, Porites rus and Porites cylindrica , from warmer inshore and cooler offshore reef systems in Palau. While these corals harbored a similar kind of symbiont in the genus Cladocopium (within the ITS2 C15 subclade), rapidly evolving genetic markers revealed evolutionarily diverged lineages corresponding to each Porites species living in each reef habitat. Furthermore, these closely related Cladocopium lineages were differentiated by their densities in host tissues, cell volume, chlorophyll concentration, gross photosynthesis, and photoprotective pathways. When assessed using several physiological proxies, these previously undifferentiated symbionts contrasted in their tolerance to thermal stress. Symbionts within P . cylindrica were relatively unaffected by exposure to 32℃ for 14 days, whereas P . rus colonies lost substantial numbers of photochemically compromised symbionts. Heating reduced the ability of the offshore symbiont associated with P . rus to translocate carbon to the coral. By contrast, high temperatures enhanced symbiont carbon assimilation and delivery to the coral skeleton of inshore P . cylindrica . This study indicates that large physiological differences exist even among closely related symbionts, with significant implications for thermal susceptibility among reef‐building Porites .

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Stabilization of myeloid-derived HIFs promotes vascular regeneration in retinal ischemia - Pilar Villacampa; Sidath E. Liyanage; Izabela P. Klaska; Enrico Cristante; Katja E. Menger; Robert D. Sampson; Maeve Barlow; Laura Abelleira-Hervas; Yanai Duran; Alexander J. Smith; Robin R. Ali; Ulrich F. O. Luhmann; et al. (Angiogenesis, 2020)
The retinal vasculature is tightly organized in a structure that provides for the high metabolic demand of neurons while minimizing interference with incident light. The adverse impact of retinal vascular insufficiency is mitigated by adaptive vascular regeneration but exacerbated by pathological neovascularization. Aberrant growth of neovessels in the retina is responsible for impairment of sight in common blinding disorders including retinopathy of prematurity, proliferative diabetic retinopathy, and age-related macular degeneration. Myeloid cells are key players in this process, with diverse roles that can either promote or protect against ocular neovascularization. We have previously demonstrated that myeloid-derived VEGF, HIF1, and HIF2 are not essential for pathological retinal neovascularization. Here, however, we show by cell-specific depletion of Vhl in a mouse model of retinal ischemia (oxygen-induced retinopathy, OIR) that myeloid-derived HIFs promote VEGF and bFGF expression and enhance vascular regeneration in association with improved density and organization of the astrocytic network.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Observable, low-order dynamical controls on thresholds of the Atlantic meridional overturning circulation - Richard A. Wood; José M. Rodríguez; Robin S. Smith; Laura C. Jackson; Ed Hawkins (Climate Dynamics, 2019)

Potential carbon loss from Scottish peatlands under climate change - Anna Ferretto; Rob Brooker; Matt Aitkenhead; Robin Matthews; Pete Smith (Regional Environmental Change, 2019)

Delivering Sustained, Coordinated, and Integrated Observations of the Southern Ocean for Global Impact - Louise Newman; Petra Heil; Rowan Trebilco; Katsuro Katsumata; Andrew Constable; Esmee van Wijk; Karen Assmann; Joana Beja; Phillippa Bricher; Richard Coleman; Daniel Costa; Steve Diggs; et al. (Frontiers in Marine Science, 2019)

Continental drift, plateau uplift, and the evolutions of monsoon and arid regions in Asia, Africa, and Australia during the Cenozoic - Xiaodong Liu; Buwen Dong; Zhi-Yong Yin; Robin S. Smith; Qingchun Guo (Science China Earth Sciences, 2019)

Identification and characterization of a novel anti-inflammatory lipid isolated from Mycobacterium vaccae, a soil-derived bacterium with immunoregulatory and stress resilience properties - David G. Smith; Roberta Martinelli; Gurdyal S. Besra; Petr A. Illarionov; Istvan Szatmari; Peter Brazda; Mary A. Allen; Wenqing Xu; Xiang Wang; László Nagy; Robin D. Dowell; Graham A. W. Rook; et al. (Psychopharmacology, 2019)

Ocean circulation drifts in multi-millennial climate simulations: the role of salinity corrections and climate feedbacks - Jennifer E. Dentith; Ruza F. Ivanovic; Lauren J. Gregoire; Julia C. Tindall; Robin S. Smith (Climate Dynamics, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

Erratum to: Intercomparison of the Arctic sea ice cover in global ocean–sea ice reanalyses from the ORA-IP project - Matthieu Chevallier; Gregory C. Smith; Frédéric Dupont; Jean-François Lemieux; Gael Forget; Yosuke Fujii; Fabrice Hernandez; Rym Msadek; K. Andrew Peterson; Andrea Storto; Takahiro Toyoda; Maria Valdivieso; et al. (Climate Dynamics, 2017)

Intercomparison of the Arctic sea ice cover in global ocean–sea ice reanalyses from the ORA-IP project - Matthieu Chevallier; Gregory C. Smith; Frédéric Dupont; Jean-François Lemieux; Gael Forget; Yosuke Fujii; Fabrice Hernandez; Rym Msadek; K. Andrew Peterson; Andrea Storto; Takahiro Toyoda; Maria Valdivieso; et al. (Climate Dynamics, 2017)

Harnessing the Potential of Human Pluripotent Stem Cells and Gene Editing for the Treatment of Retinal Degeneration - Patrick Ovando-Roche; Anastasios Georgiadis; Alexander J. Smith; Rachael A. Pearson; Robin R. Ali (Current Stem Cell Reports, 2017)

Removal of extracellular coat from giant sperm in female receptacle induces sperm motility in Mytilocypris mytiloides (Cyprididae, Ostracoda, Crustacea) - Renate Matzke-Karasz; Robin J. Smith; Martin Heß (Cell and Tissue Research, 2017)

The unseen invaders: introduced earthworms as drivers of change in plant communities in North American forests (a meta‐analysis) - Dylan Craven; Madhav P. Thakur; Erin K. Cameron; Lee E. Frelich; Robin Beauséjour; Robert B. Blair; Bernd Blossey; James Burtis; Amy Choi; Andrea Dávalos; Timothy J. Fahey; Nicholas A. Fisichelli; et al. (Global Change Biology, 2017)
Globally, biological invasions can have strong impacts on biodiversity as well as ecosystem functioning. While less conspicuous than introduced aboveground organisms, introduced belowground organisms may have similarly strong effects. Here, we synthesize for the first time the impacts of introduced earthworms on plant diversity and community composition in North American forests. We conducted a meta‐analysis using a total of 645 observations to quantify mean effect sizes of associations between introduced earthworm communities and plant diversity, cover of plant functional groups, and cover of native and non‐native plants. We found that plant diversity significantly declined with increasing richness of introduced earthworm ecological groups. While plant species richness or evenness did not change with earthworm invasion, our results indicate clear changes in plant community composition: cover of graminoids and non‐native plant species significantly increased, and cover of native plant species (of all functional groups) tended to decrease, with increasing earthworm biomass. Overall, these findings support the hypothesis that introduced earthworms facilitate particular plant species adapted to the abiotic conditions of earthworm‐invaded forests. Further, our study provides evidence that introduced earthworms are associated with declines in plant diversity in North American forests. Changing plant functional composition in these forests may have long‐lasting effects on ecosystem functioning.

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Estimates of local biodiversity change over time stand up to scrutiny - Mark Vellend; Maria Dornelas; Lander Baeten; Robin Beauséjour; Carissa D. Brown; Pieter De Frenne; Sarah C. Elmendorf; Nicholas J. Gotelli; Faye Moyes; Isla H. Myers‐Smith; Anne E. Magurran; Brian J. McGill; et al. (Ecology, 2017)
We present new data and analyses revealing fundamental flaws in a critique of two recent meta‐analyses of local‐scale temporal biodiversity change. First, the conclusion that short‐term time series lead to biased estimates of long‐term change was based on two errors in the simulations used to support it. Second, the conclusion of negative relationships between temporal biodiversity change and study duration was entirely dependent on unrealistic model assumptions, the use of a subset of data, and inclusion of one outlier data point in one study. Third, the finding of a decline in local biodiversity, after eliminating post‐disturbance studies, is not robust to alternative analyses on the original data set, and is absent in a larger, updated data set. Finally, the undebatable point, noted in both original papers, that studies in the ecological literature are geographically biased, was used to cast doubt on the conclusion that, outside of areas converted to croplands or asphalt, the distribution of biodiversity trends is centered approximately on zero. Future studies may modify conclusions, but at present, alternative conclusions based on the geographic‐bias argument rely on speculation. In sum, the critique raises points of uncertainty typical of all ecological studies, but does not provide an evidence‐based alternative interpretation.

Can savanna burning projects deliver measurable greenhouse emissions reductions and sustainable livelihood opportunities in fire-prone settings? - Jeremy Russell-Smith; Catherine Monagle; Margaret Jacobsohn; Robin L. Beatty; Bibiana Bilbao; Adriana Millán; Hebe Vessuri; Isabelle Sánchez-Rose (Climatic Change, 2017)

Trends and management implications of human‐influenced life‐history changes in marine ectotherms - Asta Audzijonyte; Elizabeth Fulton; Malcolm Haddon; Fay Helidoniotis; Alistair J Hobday; Anna Kuparinen; John Morrongiello; Anthony DM Smith; Judy Upston; Robin S Waples (Fish and Fisheries, 2016)
Evidence is accumulating that many marine ectotherms are undergoing rapid changes in their life‐history characteristics. These changes have been variously attributed to fisheries‐induced evolution, inhibited adult growth rate due to oxygen limitation at higher temperatures, and plastic responses to density dependence or changes in ocean productivity. Here, we review the diverse underlying mechanisms by which plastic and evolutionary responses to climate change and fisheries are likely to produce similar life‐history trends in harvested marine ectotherms, leading to faster life‐histories with earlier maturation and smaller adult size‐at‐age. While mechanistically understanding these growth and maturation changes may be difficult, it is becoming clear that changing life‐histories will lead to modified population dynamics, productivity and natural mortality of the affected species. We discuss how the observed and expected life‐history changes could affect the assumptions and uncertainty within single and multispecies models currently used in marine ecosystem management, highlighting that models which allow for dynamic life‐history traits often report significantly different estimates of stock biomass. Given that both climate‐ and harvest‐induced life‐history changes are likely to intensify and possibly amplify each other, there is an urgent need to adequately assess the implications of faster life‐histories for marine ecosystem management. This is especially true for data‐poor stocks, where growth and maturation are not regularly assessed. Targeted monitoring can be used to inform responsive management, but for improved sustainability outcomes, a precautionary approach to management that is robust to life‐history trends is advised.

Sperm length variations in five species of cypridoidean non-marine ostracods (Crustacea) - Robin J. Smith; Renate Matzke-Karasz; Takahiro Kamiya (Cell and Tissue Research, 2016)

Irreducible uncertainty in near-term climate projections - Ed Hawkins; Robin S. Smith; Jonathan M. Gregory; David A. Stainforth (Climate Dynamics, 2016)

Combination of herbivore removal and nitrogen deposition increases upland carbon storage - Stuart W. Smith; David Johnson; Samuel L. O. Quin; Kyle Munro; Robin J. Pakeman; René van der Wal; Sarah J. Woodin (Global Change Biology, 2015)
Ecosystem carbon (C) accrual and storage can be enhanced by removing large herbivores as well as by the fertilizing effect of atmospheric nitrogen (N) deposition. These drivers are unlikely to operate independently, yet their combined effect on aboveground and belowground C storage remains largely unexplored. We sampled inside and outside 19 upland grazing exclosures, established for up to 80 years, across an N deposition gradient (5–24 kg N ha −1 yr −1 ) and found that herbivore removal increased aboveground plant C stocks, particularly in moss, shrubs and litter. Soil C storage increased with atmospheric N deposition, and this was moderated by the presence or absence of herbivores. In exclosures receiving above 11 kg N ha −1 year −1 , herbivore removal resulted in increased soil C stocks. This effect was typically greater for exclosures dominated by dwarf shrubs ( Calluna vulgaris ) than by grasses ( Molinia caerulea ). The same pattern was observed for ecosystem C storage. We used our data to predict C storage for a scenario of removing all large herbivores from UK heathlands. Predictions were made considering herbivore removal only (ignoring N deposition) and the combined effects of herbivore removal and current N deposition rates. Predictions including N deposition resulted in a smaller increase in UK heathland C storage than predictions using herbivore removal only. This finding was driven by the fact that the majority of UK heathlands receive low N deposition rates at which herbivore removal has little effect on C storage. Our findings demonstrate the crucial link between herbivory by large mammals and atmospheric N deposition, and this interaction needs to be considered in models of biogeochemical cycling.

Invertebrate diversity of the unexplored marine western margin of Australia: taxonomy and implications for global biodiversity - Gary C. B. Poore; Lynda Avery; Magda Błażewicz-Paszkowycz; Joanna Browne; Niel L. Bruce; Sarah Gerken; Chris Glasby; Elizabeth Greaves; Anna W. McCallum; David Staples; Anna Syme; Joanne Taylor; et al. (Marine Biodiversity, 2015)

Productivity enhances benthic species richness along an oligotrophic I ndian O cean continental margin - Anna W. McCallum; Skipton Woolley; Magda Błażewicz‐Paszkowycz; Joanna Browne; Sarah Gerken; Rudy Kloser; Gary C. B. Poore; David Staples; Anna Syme; Joanne Taylor; Genefor Walker‐Smith; Alan Williams; et al. (Global Ecology and Biogeography, 2015)
Aims Marine soft sediments cover much of the deep ocean and are one of the largest habitats in the world, yet much of our understanding about their diversity is based on sampling in the N orth A tlantic. The deep‐sea benthos provides a simplified environment in which to explore the processes which maintain species richness. Here we investigate the influence of energy and habitat complexity on benthic species richness along an oligotrophic continental margin within the I ndian O cean. Location The upper continental margin of western A ustralia ( c . 13–35° S , 100–1000 m depth). Methods We examined the species richness of selected polychaetes ( A nnelida) and crustaceans in sediment grab samples. We used generalized linear models and hierarchical partitioning to examine the relationship and relative importance of temperature, productivity (particulate organic carbon flux, net primary productivity and depth) and habitat complexity (sediment particle size diversity and grain size) on species richness at 51 sites. Results In contrast to benthic studies in the N orth A tlantic, we found that species richness was higher on the shelf than on the slope. Species richness was positively correlated with net primary productivity; this relationship was influenced by high species richness in two areas where oceanic mixing is known to enhance primary productivity. Habitat heterogeneity and temperature were less influential. Main conclusion This study represents one of the first extensive quantitative studies of deep‐water benthos in the I ndo‐ W est P acific, and provides further evidence that bathymetric gradients of species richness are variable between regions, probably due to variation in local oceanography and productivity regimes. Our findings provide support for the overriding influence of productivity on species richness, even over relatively small ranges in depth and productivity. As climate change is expected to modify biogeochemical fluxes to the deep seafloor, this is likely to affect the communities of deep‐sea fauna.

Factor analytic and reduced animal models for the investigation of additive genotype-by-environment interaction in outcrossing plant species with application to a Pinus radiata breeding programme - Brian R. Cullis; Paul Jefferson; Robin Thompson; Alison B. Smith (Theoretical and Applied Genetics, 2014)

Graphical cogeneration analysis for site utility systems - Li Sun; Steve Doyle; Robin Smith (Clean Technologies and Environmental Policy, 2014)

Biodiversity patterns of nutrient-rich fish ponds and implications for conservation - A. Wezel; B. Oertli; V. Rosset; F. Arthaud; B. Leroy; R. Smith; S. Angélibert; G. Bornette; D. Vallod; J. Robin (Limnology, 2014)

The Tropical Peatland Plantation-Carbon Assessment Tool: estimating CO2 emissions from tropical peat soils under plantations - Jenny Farmer; Robin Matthews; Pete Smith; Jo U. Smith (Mitigation and Adaptation Strategies for Global Change, 2014)

Optimizing Carbon Storage Within a Spatially Heterogeneous Upland Grassland Through Sheep Grazing Management - Stuart W. Smith; Charlotte Vandenberghe; Astley Hastings; David Johnson; Robin J. Pakeman; René van der Wal; Sarah J. Woodin (Ecosystems, 2014)

Milling plant and soil material in plastic tubes over-estimates carbon and under-estimates nitrogen concentrations - Stuart W. Smith; A. H. Jean Robertson; Andrew A. Meharg; Robin J. Pakeman; David Johnson; Sarah J. Woodin; René van der Wal (Plant and Soil, 2013)

A bivariate mixed model approach for the analysis of plant survival data - Aanandini Ganesalingam; Alison B. Smith; Cameron P. Beeck; Wallace A. Cowling; Robin Thompson; Brian R. Cullis (Euphytica, 2013)

Early Eocene plant diversity and dynamics in the Falkland flora, Okanagan Highlands, British Columbia, Canada - Robin Y. Smith; James F. Basinger; David R. Greenwood (Palaeobiodiversity and Palaeoenvironments, 2012)

Maternal Immune Activation Increases Neonatal Mouse Cortex Thickness and Cell Density - Stephen E. P. Smith; Robin M. Elliott; Matthew P. Anderson (Journal of Neuroimmune Pharmacology, 2012)

The last glacial cycle: transient simulations with an AOGCM - Robin S. Smith; Jonathan Gregory (Climate Dynamics, 2012)

Impact of precipitation dynamics on net ecosystem productivity - William Parton; Jack Morgan; David Smith; Stephen Del Grosso; Lara Prihodko; Dan LeCain; Robin Kelly; Susan Lutz (Global Change Biology, 2012)
Net ecosystem productivity ( NEP ) was measured on shortgrass steppe ( SGS ) vegetation at the USDA C entral P lains E xperimental R ange in northeastern C olorado from 2001 to 2003. Large year‐to‐year differences were observed in annual NEP , with >95% of the net carbon uptake occurring during M ay and J une. Low precipitation during the 2002 A pril to J une time period greatly reduced annual net carbon uptake. Large precipitation events (>10 mm day −1 ) promoted carbon uptake, while small precipitation events ( −1 ) enhanced heterotrophic respiration and resulted in a net loss of carbon from the system. Large precipitation event enhanced carbon uptake was attributed to increased soil water content ( SWC ), which promotes plant photosynthesis. The large precipitation events which occurred from J uly to O ctober have lower increases in daytime net CO 2 uptake ( NEP d ) due to the presence of low live plant biomass compared to earlier in the growing season. Live aboveground plant biomass ( AGB ), solar radiation, and SWC were the major variables that controlled NEP d , while AGB , SWC , and relative humidity control nighttime respiration losses ( NEP n ). Aboveground plant biomass is the most important variable for controlling both NEP d and NEP n dynamics. These results suggest that the major factor controlling growing season NEP n is the amount of carbon fixed via photosynthesis during the day. Heterotrophic soil respiration is greatly enhanced for one to 2 days following rainfall events with daily rainfall events >5 mm having a similar increase in respiration (>3.00 g m Cm −2 day −1 ). In addition, the size of the heterotrophic respiration pulse is independent of both the amount of time since the last rainfall event and the time of occurrence during the growing season.

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Summary of Confirmation Cut Point Discussions - Holly W. Smith; Michael Moxness; Robin Marsden (The AAPS Journal, 2011)

Developing carbon budgets for UK agriculture, land-use, land-use change and forestry out to 2022 - Dominic Moran; Michael MacLeod; Eileen Wall; Vera Eory; Alistair McVittie; Andrew Barnes; R. M. Rees; Cairistiona F. E. Topp; Guillaume Pajot; Robin Matthews; Pete Smith; Andrew Moxey (Climatic Change, 2011)

Mitochondrial DNA evidence for the spread of Pacific rats through Oceania - Elizabeth Matisoo-Smith; Judith Robins (Biological Invasions, 2009)

Strengthening the reporting of genetic association studies (STREGA): an extension of the STROBE Statement - Julian Little; Julian P. T. Higgins; John P. A. Ioannidis; David Moher; France Gagnon; Erik von Elm; Muin J. Khoury; Barbara Cohen; George Davey-Smith; Jeremy Grimshaw; Paul Scheet; Marta Gwinn; et al. (Human Genetics, 2009)

Factors influencing anthropogenic carbon dioxide uptake in the North Atlantic in models of the ocean carbon cycle - Robin S. Smith; Jochem Marotzke (Climate Dynamics, 2008)

Maintenance of cyanotoxin production by cryopreserved cyanobacteria in the New Zealand culture collection - Susanna A. Wood; Lesley L. Rhodes; Serean L. Adams; Janet E. Adamson; Kirsty F. Smith; John F. Smith; H. Robin Tervit; S. Craig Cary (New Zealand Journal of Marine and Freshwater Research, 2008)
A culture collection of freshwater planktonic and benthic cyanobacteria collected from sites across New Zealand has been established at the Cawthron Institute, Nelson, New Zealand. Limited resources led to uncertainty regarding the long‐term maintenance of this collection. The present study demonstrates cryopreservation to be a viable method for long‐term storage of cyanobacteria. Seventeen of 20 strains evaluated were successfully cryopreserved using the permeating cryopreservation agent dimethyl sulfoxide (Me 2 SO), at a final concentration of 15% (v/v). Cyanotoxin analysis was undertaken on selected strains known to produce microcystins, nodularin, anatoxin‐a, and saxitoxins. All strains retained their ability to produce these toxins following cryopreservation.

Copulatory behaviour and sexual morphology of three Fabaeformiscandona Krstić, 1972 (Candoninae, Ostracoda, Crustacea) species from Japan, including descriptions of two new species - Robin J. Smith; Takahiro Kamiya (Hydrobiologia, 2007)

Improving fluorometry as a source tracking method to detect human fecal contamination - Peter G. Hartel; Jennifer L. McDonald; Lisa C. Gentit; Sarah N. J. Hemmings; Karen Rodgers; Katy A. Smith; Carolyn N. Belcher; Robin L. Kuntz; Yaritza Rivera-Torres; Ernesto Otero; Eduardo C. Schröder (Estuaries and Coasts, 2007)

A maternal hypomethylation syndrome presenting as transient neonatal diabetes mellitus - D. J. G. Mackay; S. E. Boonen; J. Clayton-Smith; J. Goodship; J. M. D. Hahnemann; S. G. Kant; P. R. Njølstad; N. H. Robin; D. O. Robinson; R. Siebert; J. P. H. Shield; H. E. White; et al. (Human Genetics, 2006)

DNA and meristic evidence for two species of giant stargazer (Teleostei: Uranoscopidae: Kathetostoma) in New Zealand waters - Peter J. Smith; Robin P. McPhee; Clive D. Roberts (New Zealand Journal of Marine and Freshwater Research, 2006)
The taxonomic status of the banded giant stargazer in New Zealand waters is uncertain. Mitochondrial DNA partial sequences of the cytochrome b gene and the control region, along with three meristic characters (numbers of dorsal fin rays, anal fin rays, and vertebrae), were compared among six recognised species of Kathetostoma and specimens of the banded giant morph. New Zealand specimens referred to as banded giant stargazer were shown to be a discrete species distinguished from the giant stargazer K. giganteum from New Zealand and the banded K. laeve and K. canaster from Australia, by cytochrome b and control region sequences and meristic counts. This undescribed species occurs over a wide geographic range from the Snares shelf (48°S) to the Norfolk Ridge (32°S) in the Tasman Sea, and is largely sympatric with K. giganteum. The two New Zealand species occupy different depth ranges, with the banded giant stargazer generally occurring in shallower water ( K. giganteum (12–1000 m).

Variable growth rates of the tropical estuarine fish barramundi Lates calcarifer (Bloch) under different freshwater flow conditions - J. Robins; D. Mayer; J. Staunton‐Smith; I. Halliday; B. Sawynok; M. Sellin (Journal of Fish Biology, 2006)
Relationships between freshwater flows and growth rates of the opportunistic predatory finfish barramundi Lates calcarifer in a dry tropical estuary were examined using data from a long‐term tag‐recapture programme. Lagged effects were not investigated. After accounting for length at release, time at liberty and seasonal variation ( e.g. winter, spring, summer and autumn), growth rates were significantly and positively related to fresh water flowing to the estuary. Effects were present at relatively low levels of freshwater flow ( i.e. 2·15 m 3 s −1 , the 5th percentile of the mean flow rate experienced by fish in the study during time at liberty). The analysis, although correlative, provides quantitative evidence to support the hypothesis that freshwater flows are important in driving the productivity of estuaries and can improve growth of species high in the trophic chain.

Effects of Ractopamine HCl on Escherichia coli O157:H7 and Salmonella In Vitro and on Intestinal Populations and Fecal Shedding in Experimentally Infected Sheep and Pigs - Thomas S. Edrington; Todd R. Callaway; David J. Smith; Ken J. Genovese; Robin C. Anderson; David J. Nisbet (Current Microbiology, 2006)

Six New Species of Fresh and Brackish Water Ostracods (Crustacea) from Yakushima, Southern Japan - Robin J. Smith; Takahiro Kamiya (Hydrobiologia, 2006)

Alteration paragenesis and mineral chemistry of the Tjårrojåkka apatite–iron and Cu (-Au) occurrences, Kiruna area, northern Sweden - Åsa Edfelt; Robin N. Armstrong; Martin Smith; Olof Martinsson (Mineralium Deposita, 2005)

The ontogeny of the entocytherid ostracod Uncinocythere occidentalis (Kozloff & Whitman, 1954) Hart, 1962 (Crustacea) - Robin J. Smith; Takahiro Kamiya (Hydrobiologia, 2005)

The ontogeny of Loxoconcha japonica Ishizaki, 1968 (Cytheroidea, Ostracoda, Crustacea) - Robin J. Smith; Takahiro Kamiya (Hydrobiologia, 2003)

The Ontogeny of Neonesidea oligodentata (Bairdioidea, Ostracoda, Crustacea) - Robin J. Smith; Takahiro Kamiya (Hydrobiologia, 2002)

The ontogeny of the cypridid ostracod Eucypris virens (Jurine, 1820) (Crustacea, Ostracoda) - Robin J. Smith; Koen Martens (Hydrobiologia, 2000)

The morphology of the upper lip of Cypridoidea ostracods: taxonomic and phylogenetic significance - Robin J. Smith (Hydrobiologia, 2000)

Growth limitation in young Euphausia superba under field conditions - Robin M. Ross; Langdon B. Quetin; Karen S. Baker; Maria Vernet; Raymond C. Smith (Limnology and Oceanography, 2000)
Growth rates of late furcilia and juvenile Antarctic krill ( Euphausia superba Dana) in the spring and summer were related to food quantity and quality. The 4 yr covered by this study (1991–1992, 1993–1994, 1994–1995, and 1995–1996) were part of the seasonal time series of the Palmer Long‐Term Ecological Research program. Chlorophyll a concentrations represented food quantity, and accessory photosynthetic pigments represented phytoplank‐ton community composition or food quality. Instantaneous growth rates reflected the in situ nutritional history of the previous intermolt period. The response of krill to the food environment was seen on temporal scales of days to weeks. Percent growth per intermolt period (percentage growth IMP −1 ( varied significantly both within and between years, ranging from ∼2 to 10% IMP −1 . Percent growth IMP −1 increased with increasing chlorophyll a (Chl a ), reaching a maximum of 9.3% IMP −1 above a critical concentration of about 3.5 mg m 23 . Maximum growth was reached in only 2 yr, 1991–1992 and 1995–1996. In a multiple regression analysis, total Chl a and prymnesiophyte‐Chl a explained over 71% of the temporal variance in growth. In general, highest growth was found toward the end of diatom blooms and lowest during periods of low phytoplankton biomass or blooms dominated by cryptophytes and prymnesiophytes. The results of this study support the hypothesis that maximum growth rates are only possible during diatom blooms and that production in Antarctic krill is limited by both food quantity and quality.

The Palmer LTER: A Long-Term Ecological Research Program at Palmer Station, Antarctica - Raymond Smith; Karen Baker; William Fraser; Eileen Hofmann; David Karl; John Klink; Langdon Quentin; Barbara Prezelin; Robin Ross; Wayne Trivelpiece; Maria Vernet (Oceanography, 1995)